SD Alam Bandung in encouraging the improvement of students’ reading and writing literacy skills - Abduh, Yunnisa Nabila Putri; Anwar, Rully Khairul; Lusiana, Elnovani (Berkala Ilmu Perpustakaan dan Informasi, 2025)
Introduction. This research aims to determine how literacy activities are implemented in the learning model with nature at SD Alam Bandung. This is also to analyze the role of managers in improving students literacy skills. Data Collection Methods. This research uses a qualitative method with a case study approach. Data collection techniques through observation, interviews, documentation, and literature study. The subject of this research were four resource persons. Data Analysis. Data analysis techniques through data reduction, data presentation, and conclusion drawing. Results and Discussion. The results of this study show that literacy activities in the learning with nature model by SD Alam Bandung have been implemented by integrating contextual and textual approaches in each cluster. Conclusion. The literacy skills of SD Alam Bandung students, which were previously limited, show the increase in terms of vocabulary in students in the lower cluster, the ability to write with a larger number of middle cluster students, and the ability to compile journals in students in the upper students. The result suggested that the school provide special attention to students with suboptimal literacy skills.